Letter from the Editor - Jeri W Dunkin (Online Journal of Rural Nursing and Health Care, 2012)
It has become very evident that the issues, struggles, and stories of rural nurses are similar around the world. As the official journal of the Rural Nurse Organization, this Journal presents these rural nurses’ efforts to our readers in hope of providing a forum for rural nurses to share their stories, both from practice and research, as a way to build the body of knowledge that is rural nursing. During this month in Taipei, Taiwan, the International Counsel of Nursing (ICN) will meet and for the first time the agenda will include a program for the new International Council of Nurses Rural and Remote Nurses Network. This network developed through the work of rural nurses from around the world that began discussions of a need for such a network at the 2nd International Congress of Rural Nurses held in Toowoomba, Queensland, Australia, in 2000. The discussions and development culminated in the incorporation of the group as a network within ICN. This network will provide a global forum for rural nurses and rural nursing science, issues, and practice. The network can be accessed through the ICN website at http://www.icn.ch It is my hope that between the formal organizations for rural nurses and the forum provided by the Journal that the voice of rural nurses will grow strong.